2020
DOI: 10.1371/journal.pone.0232674
|View full text |Cite
|
Sign up to set email alerts
|

Is participation in high-status culture a signal of trustworthiness?

Abstract: Trust is essential for social interactions, cooperation and social order. Research has shown that social status and common group memberships are important determinants of receiving and reciprocating trust. However, social status and group membership can coincide or diverge-with potentially different effects. Our study contributes to the existing literature on the role of status and group membership by testing two separate trust-generating mechanisms against each other. We examine if individuals tend to place t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 87 publications
2
5
0
Order By: Relevance
“…In Study 3, we found that people who prefer “lower” and “lower-middle class” music genres tend to show an ingroup bias, overrating the social class of the genre they prefer, whereas “upper-middle” and “upper-class” genres were consensually associated with the upper classes, regardless of personal preference. This is conceptually in line with Aidenberger et al’s (2020) finding that ingroup bias in trust is more pronounced among low-status (preference for folk music) than among high-status (preference for classical music) participants. The greater bias among those who prefer “lower-class” genres may reflect ingroup-protective motivation in line with social identity theorizing (Tajfel & Turner, 1979).…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…In Study 3, we found that people who prefer “lower” and “lower-middle class” music genres tend to show an ingroup bias, overrating the social class of the genre they prefer, whereas “upper-middle” and “upper-class” genres were consensually associated with the upper classes, regardless of personal preference. This is conceptually in line with Aidenberger et al’s (2020) finding that ingroup bias in trust is more pronounced among low-status (preference for folk music) than among high-status (preference for classical music) participants. The greater bias among those who prefer “lower-class” genres may reflect ingroup-protective motivation in line with social identity theorizing (Tajfel & Turner, 1979).…”
Section: Discussionsupporting
confidence: 89%
“…Looking at the extremes of the social spectrum, rap-hip hop was consistently perceived as typical of the lower class and classical music as typical of the upper class. The consensual association between music taste and social class is in line with the few existing studies, conducted in other countries (Aidenberger et al, 2020; Rentfrow et al, 2009), and confirms the idea that, in the eye of the observer, artistic preferences are markers of social standing, and hence are interpreted as status symbols (Goffman, 1951; Kraus et al, 2017).…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Thus, the higher a person's social status in society, the more privileged his position in society will be (Kim et al, 2020). According to Aidenberger et al (2020), people who have high social status are also connected with noble and trustworthy behavior because of their honesty.…”
Section: Discussionmentioning
confidence: 99%